Zaufanie a stosunki osobiste - Budnik, Christian (Filozofia Publiczna i Edukacja Demokratyczna, 2015)
Trust is a pervasive phenomenon in our lives. We trust our family members and lovers, our physicians and teachers, our politicians and even strangers on the street. Trust has instrumental value for us, but at the same time it is often accompanied by risk. This is the reason why it is important to distinguish trust that is warranted or justified from blind trust. In order to answer the question how trust is justified, however, it is crucial to know exactly what is the fundamental nature of trust. In the paper, I reconstruct three accounts of trust that operate with the assumption that trust is fundamentally a mental state – the cognitivist account, the voluntaristic account and the affect-based account. I argue that all of these accounts make reference to deeply held intuitions about trust that are incompatible with each other. As a solution to this unfortunate dialectical situation, I suggest to give up the assumption that trust is primarily a mental state. Instead, I argue for a position according to which trust is best understood as a two-place predicate that characterizes a specific relationship in which we can stand to each other.